PENERAPAN MODEL STAD DALAM MENINGKATKAN PEMAHAMAN ISI TEKS DESKRIPSI PADA PESERTA DIDIK KELAS XI - Arfian Zhulfia Isnaini; Sintowati Rini Utami; Mutmainah (Jurnal Bastra (Bahasa dan Sastra), 2024)
This study aims to apply the STAD type cooperative learning model in improving the understanding of the contents of descriptive texts in class XI students of SMA Negeri 21 Jakarta. The research method used is Classroom Action Research consisting of three cycles with four stages according to Stephen Kemmis and Robyn McTaggart, namely planning, acting, observing, and reflecting. The results of the study indicate that the application of the Student Teams Achievement Division type cooperative learning model in the learning process of each cycle can improve the understanding of class XI students of SMA Negeri 21 Jakarta regarding the contents of the descriptive text. This is indicated by an increase in the average value of students from 62.77 in cycle I, 72.92 in cycle II, and 86.61 in cycle III. Thus, students have achieved the learning objective of understanding the contents of the descriptive text well. In addition, based on the results of observations, it shows that students are more actively involved in the learning process, such as students are more actively involved in answering or asking questions, enthusiastic in following the learning process, and participating in working together as a team.